Two birds with one stone: large catalytic areas and abundant nitrogen sites inspired by fluorine doping contributing to CO2RR activity and selectivity. Issue 41 (4th October 2022) - Chen, Hongyu; Zhang, Yi; Yang, Tianfang; Shang, Yizhu; Zhu, Qiuying; Cao, Shoufu; Lin, Xiaojing; Liu, Siyuan; Wei, Shuxian; Wei, Baojun; Wang, Zhaojie; Lu, Xiaoqing
Abstract : Large catalytic areas and abundant nitrogen sites, inspired by fluorine doping, contribute to the activity and selectivity, respectively, of the CO2 RR. Abstract : Electroreduction of CO2 based on metal-free carbon catalysts is an attractive approach for useful products. However, it remains a great chemical challenge due to its unsatisfactory activity and poor selectivity. Here, we report a successful case to greatly improve CO2 -to-CO conversion on carbon black (CB) and nitrogen-doped carbon black (N-CB). By introducing fluorine, the faradaic efficiency of CO was increased from 12.8% (CB) and 50.8% (N-CB) to 93.1% (nitrogen and fluorine co-doped carbon black, N, F-CB) at −0.7 V. A partial current density of 4.19 mA cm −2 remained durable for about 23 h. The superiority of N, F-CB can be attributed to its large catalytic areas and abundant N active sites inspired by fluorine doping. Specifically, the fluorine precursor of polyvinylidene fluoride (PVDF) firstly performs as a nitrogen fixator, protecting the catalyst from more nitrogen escaping during the carbonization treatment. The number of nitrogen sites is about 4.4 times higher than it is for the N-CB. Meanwhile, PVDF as the area extender significantly improves the catalytic area; the specific surface area and the ECSA of N, F-CB are 8.7 and 6.9 times higher than that of CB. This work provides an insight into how heteroatoms can manipulate catalytic activity and selectivity through the catalytic area of carbon materials with more active sites.